AKTIVITAS PEPSIN-LIKE DAN LIPASE PADA IKAN SIDAT (Anguilla bicolor McClelland) DENGAN FASE PERKEMBANGAN BERBEDA - Muhammad Rifqi Elnanza Alba (Scripta Biologica, 2019)
The pepsin-like and lipase activities of eel with different maturity stage has been studied by an experimental method using complete randomized design (RAL) with 3 treatments and four replications. A total of 51 juvenile stage of eels (mean weight 41.25 ± 0.898 g), 14 yellow stage of eels (mean weight 319.8 ± 4.66g) and 6 silver stage of eels (mean weight 569.5 ± 9.150g) have been used for this study. Measurement of pepsin-like and lipase activities were using spectrophotometer method. The results showed that pepsin-like and lipase activities of eel did not differ significantly (P> 0.05) between different maturity stage, but pepsin-like activity was significantly different between incubation pH (P <0.05), and pH 3,4 is optimal for pepsin-like activity. Eel have equal capacity for protein and lipid digestion between different maturity stage, and has true gastric with pepsin active at acid condition (pH 3.4).